Evolution of storytelling pedagogy in global health course at a U.S. Native American-Serving Nontribal Institution from Fall 2019 to Spring 2023 - Dutta, Tapati; Keith, Camille (Frontiers in Public Health, 2023)
Background and Purpose: Responding to COVID-19 induced disruptions to traditional teaching methodologies, and considering the relevance of narratives among indigenous populations, "storytelling as pedagogy" was developed and implemented in the undergraduate Global Health course in a Native American-Serving Nontribal Institution (NASNTI) in Colorado. Methods: We describe the evolving pedagogic adjustments and storytelling strategies incorporated in the Global Health course from Fall 2019 to Spring 2023. This entailed prior to the COVID-19 in-person format, to online digital storytelling during the pandemic emergency, the HyFlex and hybrid classes with the emergence of "new normals" and finally the gradual move to in-person classes. The story arc in the course included: (1) Course Learning Outcomes revisited and the course syllabus language framed based on the Native philosophies of empowerment education, and experiential learning, (2) students' inputs sought to incorporate socio-culturally-responsive topics in the course syllabus (e.g. dental health disparities among indigenous populations), (3) strategic and non-threatening shifts such as "no textbooks" and "no finals" introduced, (4) global health thought partners invited by the course instructor and coached to use story-based teaching methods, (5) use of first-person trauma-informed storytelling methods to teach specific global health topics, and (6) students undertook gratitude journaling, a scaffolding exercise of writing letters on global health topics to global health thought partners.Results: Storytelling as pedagogy was most effective in the in-person format, while digital storytelling during the COVID-19-induced online classes was extremely challenging considering the stark digital divide in the Navajo Nation. First-person, trauma-informed storytelling is a helpful approach to discuss insider-outsider perspectives and can potentially establish sustainable trustworthy relationships among the students, instructor, and global health thought leaders. Gratitude journaling and photovoice can be tweaked as powerful storytelling methods to build students' interaction-based critical thinking, intercultural humility, and professional networking.Mapping storytelling pedagogies' best practices can be useful in developing a granulated understanding of this strategy and utilizing them across diverse disciplines in higher education. Faculty capacity building is recommended to enable the former to conceptualize culturally responsive storytelling pedagogies and create assessment plans to assess students' learning outcomes through the utilization of this method.